A comparative study of transient treampreature distribution in disc brake using explicit approaches - Azlan Aziz, 1984-; Abu Hasan Abdullah; Includes bibliographical references (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2008